Kepastian Hukum terhadap Pengajuan SHGB yang Telah Daluwarsa Menggunakan Akta Jual Beli (AJB) - Liebertha Lirung; Anang Shophan Tornado (AHKAM, 2026)
Although expired Building Use Rights (Hak Guna Bangunan/HGB) have received attention in various agrarian law studies, research that specifically discusses the legal standing of the Deed of Sale and Purchase (Akta Jual Beli/AJB) as the basis for applying for the renewal of rights after the expiration of HGB remains limited. This study aims to analyze the legal force of an AJB made while the HGB was still valid and to explore legal certainty for AJB holders in applying for the renewal of land rights. This study used a qualitative approach with a normative legal research design. Primary and secondary legal materials were obtained through documentation studies and literature searches of legislation, court decisions, books, and legal journals. The data were analyzed using qualitative analysis techniques with deductive legal reasoning. The results show that an AJB made while the HGB was still valid retains legal force as evidence of the acquisition of rights and physical control over the land, although it can no longer be used as the basis for the transfer-of-name process after the HGB has expired. These findings contribute to the development of agrarian law theory, particularly concerning legal protection for good-faith buyers in land administration practices. The conclusion of this study affirms that good faith, the validity of the AJB at the time it was made, and actual physical control of the land are important factors in applying for the renewal of land rights. The implications of this study include strengthening the literature on land registration law and providing practical recommendations for the National Land Agency (BPN) in formulating a clearer, more consistent, and more equitable administrative mechanism for granting new rights over state land. This study also opens opportunities for further research on socio-legal aspects in the variation of land policy implementation across regions.